Observation on Soil Liquefaction Analysis at Uttara Depot of Dhaka MRT Line 6 - Sayeem, Arafat Chowdhury; Islam, Shafiqul; Musfikuzzaman, Md.; Mridha, Masum (Institut Teknologi Sepuluh Nopember, 2025)
The Dhaka Metro Rail Line 6, also known as DMRT Line 6, is the first metro rail megaproject in Bangladesh which is undertaken by the government owned autonomous institution named Dhaka Mass Transit Company Limited (DMTCL). The Dhaka MRT Line-6 project consists of eight packages in total from CP (Contract Package)-01 to CP-08. The CP-01 package covers the construction of a depot at Diabari in Uttara, Dhaka. This package includes the soil improvement and land development for the construction of embankment at depot area. As CP-01 is a land development project, this project is sensitive to various geotechnical challenges, so it is obvious to identify and mitigate the geotechnical concerns associated with the project. This research analyses the potential of soil liquefaction which is a prime geotechnical challenge for this project at different boreholes of the depot. The required data is taken from the soil test report of three major boreholes (NDP-02, NDP-08 and NDP-11) at depot area and the analysis is then done according to the Seed and Idriss formula. Finally, the Factor of Safety (FL) at different depths of the soil is represented graphically to understand the overall potentiality of liquefaction with subsoil condition of the depot area.